System Diagnostics and Monitoring of Socio-Economic and Tourist Potential of Peripheral Territories of the Region - KAZAKOV, Mikhail; GLADILIN, Vladimir; MIROKHINA, Alla; DRANNIKOVA, Elena; NAROZHNAYA, Galina (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
The paper defines a heuristic task to formulate and approve methodological provisions on the system diagnostics and monitoring of the socio-economic and tourist potential of peripheral territories in the regions which are the basis for planning and implementing spatial and economic transformations. This area of scientific and methodological research and development is relevant because of the need for searching reserves for the advancement of territories based on the inventory taking and the fullest use of available resource opportunities. In this regard, the article has improved the organizational and methodological approaches to conduct monitoring as a part of a comprehensive system diagnostics of peripheral territories of the region based on analytical criteria for socio-economic and tourist potential. The authors formulated a semantic and economic interpretation of the findings and outlined the prospects for using them when forming socio-economic development policy of regions and their economy sectors. The scientific novelty of the present article consists in development of elements of system research and diagnostic methodology with respect to development potential of peripheral areas, based on the analysis of the socio-economic and tourism factors. The combination of results and recommendations represents a contribution to the scientific substantiation of spatial and sectoral analysis.